Peran Manajemen Risiko dan Inovasi dalam Memoderasi Pengaruh Fee Based Income terhadap Perubahan Laba Bank BUMN - Ramadhani Putri Sasongko , Allia; Ariany Mahastanti, Linda (IPB University, 2023)
This study aims to determine the effect of fee-based income on profit changes and the influence of risk management and innovation as a moderator between fee-based income and profit changes in state-owned banks. This study uses secondary data from annual financial reports of 4 banks, namely BRI, BNI, BTN, and Mandiri banks published by the Indonesia Stock Exchange (IDX), www.idx.co.id and the website of each related bank in the period 2013-2022. The data processing method used in this study is panel data regression analysis and Moderated Regression Analysis (MRA) using the Eviews 12 program. Based on the results of the study, fee-based income has a positive effect on earnings changes, risk management harms earnings changes, innovation has a positive impact on profit changes, risk management can weaken the effect of fee-based income and profit changes, and innovation can strengthen the effect of fee-based income and profit changes.